EVALUASI KINERJA BATIK SOLO TRANS (STUDI KASUS : KORIDOR I KARTASURA-PALUR, SURAKARTA) - Purnomo Dwi Sujatmiko; Nadhia Puspita R.; Ismiyati Ismiyati; Wahyudi Kushardjoko (Jurnal Karya Teknik Sipil, 2013)
The results of the performance evaluation BST corridor I obtained some indicators that meet the standards of the Department of Transportation and the World Bank that headway, speed, travel time on Saturday and Sunday, as well as most of the distance between the shelter, while the load factor is still below the standard which is still less than 70 %. Load factor due to non-fulfillment by the results of the questionnaires are reluctant to switch to using BST for several reasons including watu waiting periods, the route less BST, BST facilities are lacking, long travel times BST, is also proved from the results of the survey where the travel time for the day Monday more than 3 hours. Despite the low load factor based on the analysis of vehicle operating costs BST rate applicable experience keutungan that will be able to meet the operational costs of vehicles. With the results of the analysis did not meet the standard, it can be improved by adding corridors that intersect with the corridor so that the people I want to switch to using BST as it has many routes. Making other transport as feeder so that the corridor I just BST operate and can facilitate people to the shelter BST which will be raising load factor.Contra flow system on the road Slamet Riyadi tracking and bus priority at junctions can shorten travel times BST faster. With that expected performance can be optimized BST serve passengers and non-users can switch to using a BST as a mode of daily transportation.